Antibacterial Activity of Moringa Plants (Moringa oleifera Lam.) to Overcome Antibiotic Resistance: A Systematic Review - Novitarini; Jason Merari P.; Dian Marlina (HM Publisher, 2022)
Antibiotic resistance This causes the performance of synthetic antibiotics to decrease, so it is necessary to search for natural antibiotics. Moringa plant (Moringa oleifera Lam.) has antibacterial activity proven to inhibit and kill pathogenic bacteria and Multi-Drug Resistance (MDR)article review aims to collect data related to testing the antibacterial activity of Moringa plants as an effort to overcome antibiotic resistance. The method follows the PRISMA-2020 protocol by searching data on PubMed and ScienceDirect media using the keywords: